Pattern of refractive errors among the Nepalese population: a retrospective study - Shrestha, SP; Bhat, KS; Binu, VS; Barthakur, R; Natarajan, M; Subba, SH (Nepalese Journal of Ophthalmology, 2010)
Introduction: Refractive errors are a major cause of visual impairment in the population. Purpose: To find the pattern of refractive errors among patients evaluated in a tertiary care hospital in the western region of Nepal. Materials and methods: The present hospital-based retrospective study was conducted in the Department of Ophthalmology of the Manipal Teaching Hospital, situated in Pokhara, Nepal. Patients who had refractive error of at least 0.5 D (dioptre) were included for the study. Results: During the study period, 15,410 patients attended the outpatient department and 10.8% of the patients were identified as having refractive error. The age of the patients in the present study ranged between 5 - 90 years. Myopia was the commonest refractive error followed by hypermetropia. There was no difference in the frequency of the type of refractive errors when they were defined using right the eye, the left eye or both the eyes. Males predominated among myopics and females predominated among hypermetropics. The majority of spherical errors was less than or equal to 2 D. Astigmatic power above 1D was rarely seen with hypermetropic astigmatism and was seen in around 13 % with myopic astigmatism. "Astigmatism against the rule" was more common than "astigmatism with the rule", irrespective of age. Conclusion: Refractive errors progressively shift along myopia up to the third decade and change to hypermetropia till the seventh decade. Hyperopic shift in the refractive error in young adults should be well noted while planning any refractive surgery in younger patients with myopia. Keywords: myopia; hypermetropia; astigmatism; ethnicities; age DOI: 10.3126/nepjoph.v2i2.3714 Nep J Oph 2010;2(2) 87-96